Pengaruh Penyusunan Laporan Keuangan, Pendidikan Pemilik, Pelatihan Akuntansi, dan Kondisi Pesaing terhadap Penggunaan Informasi Akuntansi pada Usaha Mikro Kecil, dan Menengah (UMKM) di Kota Tegal - Putri, Aulia Meiliani; Raharjo, Teguh Budi (Majors Accounting, Faculty of Economics and Business, Universitas Pancasakti Tegal, 2020)
This study aims to determine the effect of preparing financial statements, owner education, accounting training, and competitors' conditions on the use of accounting information in Micro, Small and Medium Enterprises (MSMEs) in Tegal City. This research was conducted on Micro, Small and Medium Business Owners in Tegal City. The type of data used is primary data, with a total of 100 SME respondents. The method of data collection is done by a questionnaire that is distributed electronically via google form. While the data analysis method used is multiple linear regression analysis using the SPSS 22 program. The results showed that, Preparation of Financial Statements, Owner Education, Accounting Training influenced the use of the use of accounting information at SMEs in the City of Tegal. Competitor's condition does not affect the use of accounting information in the City of Tegal.